Demixing and symmetry breaking in binary dipolar Bose-Einstein-condensate solitons - Adhikari, S. K. [UNESP] (Amer Physical Soc, 2014)
We demonstrate a fully demixed (separated) robust and stable bright binary dipolar Bose-Einstein-condensate soliton in a quasi-one-dimensional setting formed due to dipolar interactions for repulsive contact interactions. For large repulsive interspecies contact interaction, the first species may spatially separate from the second species, thus, forming a demixed configuration, which can be spatially symmetric or symmetry broken. In the spatially symmetric case, one of the species occupies the central region, whereas, the other species separates into two equal parts and stays predominantly out of this central region. In the symmetry-broken case, the two species stay side by side. Stability phase diagrams for the binary solitons are obtained. The results are illustrated with realistic values of parameters in the binary Dy-164-Er-168 and Dy-164-Dy-162 mixtures. The demixed solitons are really soliton molecules formed of two types of atoms. A proposal for creating dipolar solitons in experiments is also presented.